Sodium, potassium adenosine triphosphatase as a potential target of the anti-tuberculosis agents, clofazimine and bedaquiline - Cholo, Moloko C. (University of Pretoria, 2024)
Dissertation (MSc (Medical Immunology))--University of Pretoria, 2023.